The influence of career planning, self-confidence, and internship experience on work values that have an impact on the work readiness of SMK Students in the Tulungagung region - Sesanti, Yeni Tri; Tuwoso, Tuwoso; Atmoko, Adi; Nurjanah, Nunung (Edelweiss Applied Science and Technology, 2025)
Preparing vocational high school students to meet the demands of the job market is a significant challenge. The hypothesis suggests that students' work values, which are determinants of their work readiness, are shaped by factors including career planning, level of self-confidence, and experience in Field Work Practices (PKL). This study aims to determine the effects of career planning, self-confidence, and PKL experience on work values that impact the work readiness of vocational students in the Tulungagung area. The research utilized a quantitative methodology, specifically an ex post facto design. It is a correlational study that seeks to identify the causal phenomena related to the work readiness of vocational high school students in the Tulungagung area. The data collected were evaluated using AMOS 26.0. The results showed that self-confidence has no effect on work value, while career planning and PKL experience have positive effects on work value. This indicates that an increase in work value correlates with an increase in job readiness by 100%.